ELABORACIÓN DE UN MANUAL DE FUNCIONES DEL CENTRO MÉDICO APROFELOJA - CALDERÓN PINZA, LUCAS ABDÓN (2016)
In the development of the present thematic once applied field study, the survey addressed to workers of the Center doctor APROFE evidenced that administrative activities is them running without the use of Manual functions, thus determine it 77% of workers, a situation that leads to the subrogation of the functions, attributions of responsibility to each department or sector worker within the company establishing an environment unsuitable for the normal functioning of the institution based on hierarchies of the administration. In addition 90% of the administrative staff of the APROFE-Loja Medical Center indicate that the administrative reorganization is necessary since there is an administrative unit of the parent headquarters in Guayaquil. Therefore prepares the functions Manual establishing obligations, responsibilities and delimitation of work based on each charge is getting establish respect for the administrative hierarchical order within the institution, to ensure more than economic growth of independently to consolidate itself as a branch with its administrative base which ensures economic growth and fulfillment of the mission and institutional vision which allows the institution established as a pioneer in the provision of medical services to persons in a State of pregnancy and sex education in the southern region of the country, establishing himself as a model to be followed by the rest of branches nationwide.